2012
DOI: 10.4172/2155-9570.s4-002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Visual Cortex in Patients with High-Tension Glaucoma

Abstract: FMRI was measured by the BOLD method using a gradient-echo EPI sequence with the following parameters: TE=30 ms, TR=3 s, flip angle 90°. The measured volume consisted of 39 continual slices of 2 mm in thickness and the size of the measured voxel (spatial resolution) was 2 x 2 x 2 mm (FOV=208 x 208 mm, matrix 104 x 104, reconstruction matrix 128 x 128, SENSE factor of 1.8). FMRI was performed in all the subjects. An alternation of a black and white checkerboard (Figure 1) was shown to the subjects during the fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
0
19
1
1
Order By: Relevance
“…The cortical modifications reported here may differ from the alterations in V1 cortical responses in relation to peripheral visual loss reported in glaucoma studies (Dai et al, 2012, Duncan et al, 2007a, Duncan et al, 2007b, Engin et al, 2014, Lešták and Tintěra, 2011, Qing et al, 2010). In glaucoma, retinal ganglion cell death affects the entire visual pathway through transsynaptic degeneration (Engelhorn et al, 2011, Engin et al, 2014, Gupta et al, 2009).…”
Section: Discussioncontrasting
confidence: 74%
“…The cortical modifications reported here may differ from the alterations in V1 cortical responses in relation to peripheral visual loss reported in glaucoma studies (Dai et al, 2012, Duncan et al, 2007a, Duncan et al, 2007b, Engin et al, 2014, Lešták and Tintěra, 2011, Qing et al, 2010). In glaucoma, retinal ganglion cell death affects the entire visual pathway through transsynaptic degeneration (Engelhorn et al, 2011, Engin et al, 2014, Gupta et al, 2009).…”
Section: Discussioncontrasting
confidence: 74%
“…Studies dealing with high-tension glaucoma describe the same phenomenon. 1,14,15 One possible and currently implemented method of exudative AMD treatment is intravitreal application of anti-VEGF. Brar et al, 16 who studied the effect of bevacizumab on retinal ganglion cells in animal models, found that the effect of retinal ganglion cell protection against oxidative stress was eliminated by bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…1 The aim of this study was to use fMRI to investigate visual centres in patients with exudative form of AMD, where the retinal ganglion cells are damaged secondarily. We want to prove our hypothesis that there is a difference in fMRI activation between patients with wet AMD and control group and also that a relationship between visual acuity and fMRI activity exists.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from our study were in good agreement with that of (Qing et al 2010) whereby, for normal participants, PSD was lowest and the number of activated voxel was highest. In another study (Lešták et al 2011), it was found that the decreasing fMRI activation was associated with oxygen extraction in neurovascular link due to the reduction in the number of surviving neurons. The negative correlation means that the PSD of visual field values increases while the fMRI activation decreases.…”
Section: Discussionmentioning
confidence: 94%
“…The decrease in NOV in visual cortex for GS and POAG participants as compared to the normal, on the one hand, clearly indicates a reduction in the functionality of visual cortex in relation to visual field stimuli (Lešták et al 2011). …”
Section: Discussionmentioning
confidence: 97%